Tradução & cognição : interfaces - Dutra, Elaine Cristina Pereira (2009)
This research attempts to relate translation studies to psychology, anthropology, biology, cognitive linguistics and literature. Our objective is to demonstrate the relationship between the theory of prototype and translation. To do so, we discuss the current theoretical focus on the acquisition and learning of the first and second languages, bilingualism, the training of the translator, types of translation, and the linguistic competence related to translation. We also present the psychological cognitive processes in the act of translate: introspection, perception, abstraction, memory, thought, conceptualizing. We present the role of the prototype effect and of equivalence in translation, relating them and evaluating them, concluding that there are levels of equivalence more or less acceptable (gradient effect/prototypical) according to the judgment of the translator and that there are invariable lines (prototypes) that are perceived and perpetuated by readers and translators. So as to corroborate with the hypothesis, we analyze translated texts, seeking the effect and the presence of the prototype and we conclude that the basic level is of the highest occurrence, and reflects the net of constructions that guide the translator’s thought and memory.